CMOC system administration & maintenance procedure package for Telekom Malaysia and traffic data analysis / Sariah Ab. Ghani - Ab. Ghani, Sariah (2002)
This project thesis deals with the Concept of Centralized Operation and Maintenance and this is made possible with the existence of computerized exchanges where the self-diagnostic capability is available in the digital switching system. This concept has changed the conventional preventive and corrective maintenance method to a controlled maintenance method. CMOC system administration and Maintenance procedure for Telekom Malaysia was developed as a guideline for users to use the system effectively. This was done using Visual Basic program. The traffic data which abstracted from FETEX-150 Exchange by using CMOC station was analysed using Microsoft Excel program. Hopefully all information discussed, will give some basic knowledge on this Centralisation on switching Network for Telekom Malaysia.